PELATIHAN PENGUKURAN KUALITAS AIR UNTUK MENDUKUNG USAHA BUDIDAYA RUMPUT LAUT DI NEGERI RUTONG - Pattinasarany, Maureen M; Palinussa, Elizabeth Miklen (Universitas Mataram, 2024)
The characteristics of water quality play a role in choosing the ideal site for seaweed farming. Additionally, by using the proper cultivation techniques and methodologies, seaweed cultivation activities might be effective. Seaweed farming is often thought of as a relatively easy endeavor that can be done in any body of water. But seaweed requires several requirements. The study of water conditions in Rutong country is important in determining the location and the method should be appropriate and usable. The purpose of the activity is to provide knowledge and skills to the community on how to measure water quality parameters then for the initial development of seaweed cultivation businesses can offer seaweed cultivation methods. This activity was carried out for 1 month in May 2022 in the village of Rutong with the involvement of the start-up team. There were nine participants. Participatory active method. Communities are actively involved in observation, sampling and discussion. The result is that the salinity value of the surface water in Rutong only reaches 28 ppt on average. This is strongly suspected to be due to the supply of fresh water through the river. While temperature and brightness are suitable for aquaculture activities. The solution was to shift aquaculture activities more towards the sea. Water temperature can be supportive for seaweed cultivation in Rutong country because seaweed can live in water temperatures of 27-28℃. Aquaculture activities can use the floating method with a type of longline -raft combination so that it can float in the water column. The conclusion was that the community was actively involved and skilled in seawater sampling, measuring water quality can determine cultivation methods and cooperate in the design of rearing containers.